Three essays on the economics of land use and conservation - Shartaj, Mostafa, author; Suter, Jordan F., advisor; Manning, Dale T., committee member; Bayham, Jude, committee member; Jones, Kelly, committee member (Colorado State University. Libraries, 2024)
This dissertation consists of three chapters focused on the economics of land use and conservation. The first chapter investigates the differences in groundwater use among wells irrigating State Land Board (SLB) parcels and nearby private parcels. SLB parcels represent leased parcels with limited tenure length and uncertainty of renewal. In the chapter, we demonstrate that wells irrigating SLB lands pump substantially more groundwater compared to non-SLB wells. The second chapter makes use of a novel dataset of discount rates elicited from agricultural producers across the United States to explore how estimates of discount rates for can be utilized to improve the performance of agri-environmental programs. The final paper examines camping in US Forest Service (USFS) campgrounds during the COVID-19 pandemic. Using data on campground reservations made through recreation.gov, we illustrate how camping on USFS lands was impacted by infection rates, public health restrictions and proximity to metropolitan areas and National Parks (NPs). Imperfect property rights can lead to over-extraction of resources and provide disincentives to invest in conservation of the resource stock. In the first chapter, making use of a natural experiment, we explore the case of groundwater usage on State Land Board (SLB) parcels, relative to nearby private parcels. The SLB of Colorado leases out land to agricultural producers, with groundwater rights tied to the land leases. Leases by the SLB have tenure lengths of 10 years, where the leaseholder is allowed to renew their lease if they can match the highest bid for the next lease term. This generates uncertainty regarding access to future groundwater stocks. We contribute to the literature by demonstrating the causal impact of SLB designation on groundwater use. We show that wells irrigating SLB lands, on average, use 15 to 24 percent more groundwater compared to nearby private lands. Adoption of conservation practices in agriculture often requires upfront costs, while the private benefits are produced in the future. As such, farmers' time preferences can play an important role in adoption decisions. In the second chapter, using elicited discount rates of farmers from 26 US states, we explore the role of farmers' discount rates in cover crop adoption, program participation, and continuation of cover cropping after the contract period. The data reveal that mean observed discount rates are lower both for farmers that adopt cover cropping and for farmers that participate in conservation programs, compared to those who do not. This suggests that time preferences play a key role in conservation adoption decisions. The empirical results are followed by a simulation analysis, which utilizes the discount rate data to explore benefits of tailoring conservation contracts based on discount rates. The simulations point out that a small increase in upfront payments can substantially increase cover cropping during the contract period, but they do little to increase continuation of cover cropping after the contract period. The simulations also reveal that tailoring the contract length and annual payment, according to the discount rate information, can allow policy makers to target higher levels of continuation, which are unattainable under the 5-year status quo contract. In the extreme case where the program administrator can observe individual discount rates, it is possible to dramatically reduce the costs of increasing continual adoption by individually tailoring the contracts. During the COVID-19 pandemic, US public land managers faced the challenge of catering to large increases in camping demand, while maintaining social distancing guidelines. In the final chapter, we use multivariate linear regression to analyze weekly changes in reservations to US Forest Service (USFS) campgrounds between 2019 and 2020. Our sample includes 1,688 individual USFS campgrounds from across the contiguous US. The results illustrate the dramatic increases in camping on USFS land that occurred in the summer of 2020 and demonstrate that increases in local infection rates led to significant increases in camping nights reserved in the summer. The results also illustrate that the increase in camping nights reserved at USFS campgrounds was particularly dramatic for campgrounds located near large metropolitan areas and near National Parks that saw increases in overall recreational visits. These results point to the important role that public lands played during the pandemic and can help guide public land resource allocations for campground maintenance and operation.
Keywords: conservation; land use; outdoor recreation; groundwater; agriculture; natural experiment